Congenital reproductive abnormalities in sheep - NAQVI, S M K; PANDEY, G K; GAUTAM, K K; JOSHl, A; MITIAL, J P (The Indian Journal of Animal Reproduction, 2023)
lbree cases of congenital abnonnalities, namely Double external os, Uterus didelphys and Paraovarion cyst were observed from 250 reproductive tracts obtained from abattoir. The incidence of congenital abnormalities was 1.2% and found to be within the range reported in sheep.